Evaluation of Antiulcer Potential of Bougainvillea spectabilis Extracts on Cysteamine Hydrochloride-Induced Duodenal Ulceration in Rats (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Bougainvillea spectabilis has long been utilized for its diverse range of medicinal characteristics, including antibacterial, antiviral, hepato-protective, anti-inflammatory, antifungal, anti-diabetic, antioxidant, antifertility, antiulcer, anticancer and antiviral effects. The objective of this research was to find out how B. spectabilis (both ethanolic and aqueous extract) affected the development of duodenal ulcers. The investigation was conducted on a model of duodenal ulceration utilizing the chemical cysteamine hydrochloride, which has the potential to induce ulcers in conjunction with ranitidine, a conventional medicine. Then, a treatment group consisting of the plant’s ethanolic and aqueous extract was compared to the chemical that causes duodenal ulcers. The ethanolic extract derived from the B. spectabilis plant demonstrated a strong ability to treat duodenal ulcers produced by the chemical cysteamine hydrochloride. The ethanolic extract effectively protected the duodenum and stomach regions from chemical-induced damage, as demonstrated by its superior performance compared to the conventional treatment. Both stomach as well as duodenal ulcer healing and protection against experimentally induced duodenal ulcers in rats were improved by the plant B. spectabilis.